2000
DOI: 10.1046/j.1432-1327.2000.01146.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide and amino‐acid sequences of a new‐type pectate lyase from an alkaliphilic strain of Bacillus

Abstract: A pectate lyase (pectate transeliminase; EC 4.2.2.2), designated Pel-15E, was purified to homogeneity from a culture broth of alkaliphilic Bacillus sp. strain KSM-P15. The purified enzyme had a molecular mass of < 33 kDa, as determined by SDS/PAGE, and a pI of < pH 9.2. Pel-15E exhibited optimum activity at pH 10.5 and 50±55 8C in glycine/NaOH buffer. Pel-15E had an absolute requirement for Ca 2+ ions for manifestation of the enzymatic activity and trans-eliminated poly(galacturonic) acid, most likely by endo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Although the pure enzyme appears homogenous on SDS-PAGE and FPLC, the authors do not claim it as a totally pure preparation, since plant genomes contains several potential pectate lyase genes, which encode homologous proteins, which would be very difficult to separate by biochemical methods. The specific activity of the enzyme was 680 ± 50 pkat mg protein À1 , which was low compared to homogenous PEL from microbial sources (Crawford and Koattukuty, 1987;Liao et al, 1997;Benen et al, 2000;Sawada et al, 2000;Kluskens et al, 2003).…”
Section: Discussionmentioning
confidence: 80%
“…Although the pure enzyme appears homogenous on SDS-PAGE and FPLC, the authors do not claim it as a totally pure preparation, since plant genomes contains several potential pectate lyase genes, which encode homologous proteins, which would be very difficult to separate by biochemical methods. The specific activity of the enzyme was 680 ± 50 pkat mg protein À1 , which was low compared to homogenous PEL from microbial sources (Crawford and Koattukuty, 1987;Liao et al, 1997;Benen et al, 2000;Sawada et al, 2000;Kluskens et al, 2003).…”
Section: Discussionmentioning
confidence: 80%
“…The catalytic module of Pel10A shows 30 and 36 % identities to pectate lyase A from A. irakense [14] and pectate lyase 15E from alkaliphilic Bacillus sp. strain KSM-P15 [19], respectively ( Figure 5). Structural and sitedirected mutagenesis studies of pectate lyases have indicated the importance of arginine in substrate charge neutralization, and acidic residues as proton donors during catalysis [28,29], and indeed family 10 pectate lyases possess six invariant arginine residues, four invariant aspartic acid residues and four invariant glutamic acid residues ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…The 35.8 kDa Cterminal module of Pel10A shows similarity to pectate lyase A from Azospirillum irakense [14] and pectate lyase 15E from the alkaliphilic Bacillus sp. strain KSM-P15 [19] (Figure 5). Both the A. irakense and the Bacillus enzymes are members of family A modular pectate lyase containing a carbohydrate-binding module The proposed ribosome-binding sequence is underlined.…”
Section: Az-rhamnogalacturonan-active Enzymes From P Cellulosamentioning
confidence: 99%
“…and Ni 2? ions resulted in the recovery of the enzyme activity by 62, 36, 9 and 7%, respectively (Sawada et al 2000). Pel from banana can use Mn 2?…”
Section: Metal Ion Requirementmentioning
confidence: 98%